2017
DOI: 10.18203/issn.2454-2156.intjscirep20175936
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of frequency and risk factors for intrauterine growth restriction

Abstract: <p class="abstract"><strong>Background:</strong> <span lang="EN-IN">Intrauterine growth restricted (IUGR) fetuses are at greater risk of developing fetal hypoxia, neonatal complications, impaired neurodevelopment, and also neonatal intensive care unit stay and neonatal mortality. They are also known to develop metabolic syndrome in adult life. So, the main objective of this study was to find out the frequency of intrauterine growth restriction, to identify the maternal and placental ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…The findings showed that preeclampsia had a significant risk of increasing the SGA by 7.43 times compared to mothers who did not experience preeclampsia. It is also strengthened by the research of Shrestha (2018), which showed that maternal factors, the condition of preeclampsia, had a significant and robust relationship with the incidence of IUGR. Placenta previa is a condition where there is an abnormality in the implantation of the placenta that can partially or wholly cover the internal uterine os (OIU).…”
Section: Multivariate Analysismentioning
confidence: 94%
“…The findings showed that preeclampsia had a significant risk of increasing the SGA by 7.43 times compared to mothers who did not experience preeclampsia. It is also strengthened by the research of Shrestha (2018), which showed that maternal factors, the condition of preeclampsia, had a significant and robust relationship with the incidence of IUGR. Placenta previa is a condition where there is an abnormality in the implantation of the placenta that can partially or wholly cover the internal uterine os (OIU).…”
Section: Multivariate Analysismentioning
confidence: 94%
“…23 In the present study, other maternal risk factors contributing to SGA babies were observed and according to Shrestha et al hypothyroidism contributing to IUGR were 5%. 20 Mandhar et al found the other maternal risk factor causing IUGR were chronic renal disease, rheumatic disease, uterine anomaly, obstetric cholestasis, antiphospholipid antibodies(APLA) and chemotherapy. 21 The 107(33.12%) babies suffered from some forms of neonatal complications.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Fetal factors include aneuplodies. As effective screening measures have not yet been established, these clinical criteria have, nevertheless, demonstrated a distinct impact for each unique instance and their relevance [8].The various factors leading to IUGR were BMI<18.5kg/m 2 was found in 22 (36.7%). IUGR was observed in10(16.7%) of smoking mothers [9].…”
Section: Introductionmentioning
confidence: 99%
“…IUGR was observed in10(16.7%) of smoking mothers [9]. Preeclampsia was found in 38(19.2%), anemia in 35(17.7%), gestational diabetes mellitusin12(6.06%), hypothyroidism in 10(5.05%) and retroplacental clot was found in28(14.4%) [10].…”
Section: Introductionmentioning
confidence: 99%